Lichen Amyloidosis on the Back that improved with Methotrexate Administration: Case Report - Danil, Rezkyana; Dalimunthe, Dina A (Fakultas Kedokteran Universitas Brawijaya, 2025)
Lichen amyloidosis comprises a range of disorders characterized by amyloid protein deposits in tissues and organs. Several studies have shown that lichen amyloidosis is a form of localized primary cutaneous amyloidosis, often affecting the anterior legs and arms, but rarely found in the back, making such cases notable. A 75-year-old male presented with pruritic brown-black hyperkeratotic nodules on the back, which had increased over the past year. The patient had a history of psoriasis vulgaris and was being treated with methotrexate, cetirizine, and topical medications. Histopathology with Congo Red staining confirmed lichen amyloidosis, with amyloid deposits in the dermal papillae. Lichen amyloidosis, although typically localized to the lower extremities, may also appear on the back in rare cases. The amyloid deposition in the dermis may result from chronic friction or genetic factors. In addition, methotrexate's role in managing the condition is related to its immunosuppressive and anti-inflammatory effects. This case indicates the importance of recognizing atypical presentations of lichen amyloidosis. Early histopathological confirmation and tailored treatment, including methotrexate and topical corticosteroids, can aid symptom relief and prevent progression.